If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3(-1x + 1) = 9 Reorder the terms: x + 3(1 + -1x) = 9 x + (1 * 3 + -1x * 3) = 9 x + (3 + -3x) = 9 Reorder the terms: 3 + x + -3x = 9 Combine like terms: x + -3x = -2x 3 + -2x = 9 Solving 3 + -2x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = 9 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 9 + -3 -2x = 9 + -3 Combine like terms: 9 + -3 = 6 -2x = 6 Divide each side by '-2'. x = -3 Simplifying x = -3
| x^2+6x+5=x^2 | | 8t^2=32 | | n+3.01+3n=4n+3.01 | | 7.7=2.7+5x | | 30=3h+6 | | -8c=144 | | m/30=12/72 | | n+-9=-30 | | 2(2x+1)=-1o | | 2x-5-7x+1=4x-6x+11 | | Log(9)2+log(9)(X+2)=1 | | 2x+8=6x-10 | | 10+x=5-20 | | 18=7x+3-4x | | 2(-7+2y)+3y=0 | | 3(2x-3)=7x+21 | | Y=5x-0.5x | | 10000=x^2+x | | -6(10-4r)=-3(-12-8f) | | 10x+7-2x=x-2+8x | | 10x+7=x-2+8x | | 12-10(5x+4)+4x= | | 16*5*3.14= | | 3.14*16*5= | | 6b+4-2b=6b | | (2x+8)(3x+24)=0 | | 90+x+34+x+64=180 | | -6x^3+9x^2+6x= | | .5y-4=33.33y-3 | | y-3x=-5y | | 5x+10=5x-10 | | 23b+70=40b-100 |